Review articleStress hyperglycemia - Wawrusiewicz-Kurylonek, Natalia; Górska, Maria (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2007)
Stress hyperglycemia is the response of the organism to the stress, that is an event that cause a disturbance an internal homeostasis. The response of the organism to the stress is the activation of neuroendocrine axises and releases cytokines and humoral factors, which influence an intercellular processes. Stress hyperglycemia and insulin resistance are exceedingly common in critically ill patients. Especially exist after severe injures, operations, extensive burns, transplants and in general in patients who need intensive care at medical ICU. There are data which have shown that the intensive insulin therapy leading to normoglycemia improves prognosis in critical ill patients.